BUSINESS It's Legal, Ethical, and Global Environment - JENNINGS MOODY MARIANNE (CANADA CENGAGE LEARNING, 2012)
The book "Business: Its Legal, Ethical, and Global Environment" by Marianne Jennings provides a comprehensive guide on the intersection of business law, ethics, and regulatory frameworks in today$1 (Bs global marketplace. It emphasizes understanding how legal principles and ethical considerations influence business decisions and practices.s
BUSINESS
MANAGEMENT
BBA & MBA
Keywords: BUSINESS; MANAGEMENT